Influence of culture on risks in offshore outsourcing of software projects: A quantitative study on mum effect - Ramingwong S. (2017)
The growth of offshore outsourcing of software projects is phenomenonal. Offshore outsourcing generally occurs from developed nations to developing nations. It is undeniable that several major issues, such as culture, could subtly influence the success of such projects. Mum effect is an important risk in offshore outsourcing of software projects. The degree of intensity and probability of this particular risk is likely to be different in different cultural environments. This study investigates the relationships between mum effect and Hofstede's cultural dimensions by collecting data from hundreds of Thai IT professionals. Several mitigation strategies are also discussed. values to several © 2010 IEEE.